Analisis Sun Protection Factor (SPF) Stick Ekstrak Daun Nangka (Artocarpus heterophylla Lamk.) 2% secara In Vitro dengan Spektrofotometri UV-Vis - Adrianta, Ketut Agus; Berata, Putu Febryana Suryaputri; Suena, Ni Made Dharma Shantini (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2024)
Ultraviolet light, especially ultraviolet B (UV-B) light, can cause the formation of free radicals, namely reactive oxygen species (ROS). Jackfruit leaves are rich in phenolic compounds such as flavonoids, have good antioxidant properties, and can act as UV-protectors. Several studies using natural materials have been carried out to determine the protective activity of Jackfruit Leaf Extract (Artocarpus heterophylla Lamk.) as a UV-protector based on the Sun Protection Factor (SPF) value. This research was conducted using the in vitro method using spectrophotometry by first macerating the jackfruit leaves, then concentrating them with a rotary evaporator. The extract obtained was formulated into a stick and then dissolved into several concentrations, namely 2,500 ppm, 5,000 ppm, 7,500 ppm, and 10,000 ppm. The results showed that the SPF value at a concentration of 2,500 ppm was 8.09 (maximum protection), at a concentration of 5,000 ppm was 16.83 (ultra protection), at a concentration of 7,500 ppm was 14.34 (maximum protection), and at a concentration of 10,000 ppm (maximum protection). Based on the results of the study, a 2% stick of jackfruit leaf extract (Artocarpus heterophylla Lamk.) had the highest SPF value, namely 16.83 in the ultra-protection category at a concentration of 5,000 ppm, so it has the potential to be a UV-protector.